The mediating role of entrepreneurship in the link between high-speed rail and carbon emissions reduction - Chen, Yu; Chen, Wenqing; Chen, Shan (Frontiers in Environmental Science, 2022)
Prior studies document that the development of transportation infrastructure, particularly the rapid development of high-speed rail plays a key role in transforming an economy towards a low-carbon development mode by reducing carbon emissions in China and beyond. However, so far the mechanisms and paths that link high-speed rail to carbon emission reduction remain ambiguity and unknown. The present study thus intends to clarify this path by proposing the mediating role of entrepreneurship, arguing that the rapid cycle of people, capital, knowledge, technology induced by high-speed rails would be integrated by entrepreneurs as new start-ups, and hereby leading to industry agglomeration, upgrading, and innovations. These consequences of entrepreneurship would further result in carbon emission reductions. Employing a unique dataset in China, we provide strong evidence for our arguments by setting China’s prefecture-level cities as the unit of analysis. The empirical results illustrate that the opening of high-speed rail in cities is conductive to establishment of new start-ups, and further benefiting the city’s carbon emission reduction. Meanwhile, it is found that the administrative approval system reform would strengthen the effect of high-speed rail on entrepreneurship. This study therefore clarifies the path whereby high-speed rails executes on carbon emission reduction, and reconfirms the role of the transportation development in achieving the goal of sustainable development towards carbon neutrality.